Transformation of the prison library of Malaysian integrity school: a meaningful experience / E. R. K. Rafedzi ... [et al.] - Rafedzi, E. R. K.; Ahmad, Asmany Aza; Sulaiman, Zaidah; Ishak, Azmah; Mah Hasan, Rosmarlidaini; Abd Haris, Naqiuddin; Md Jali, Jafalizan (Faculty of Information Management, 2024)
The existence of academic classes at the Integrity School of Correctional Center indirectly encourages juvenile delinquents to use the prison library to obtain information related to their studies. The importance of the prison library, to meet the information needs of prison inmates (including the juvenile delinquents), providing materials for inmates’ studies and indirectly supporting the rehabilitation process of prison inmates. The awareness in helping the rehabilitation process of juvenile delinquents through exposure to the use of reading material as a rehabilitation tool; has encouraged the Tun Seri Lanang Library (PTSL), UKM to run a community service program at the Prison Library of Integrity School. PTSL UKM has sought advice from UiTM regarding collections and services in the prison library in order to produce a prison library model that can meet the needs of juvenile delinquents. As a result, a prison library model has been created by providing a bibliotherapy corner, improving the collection based on the needs of juvenile delinquents and brightening the prison library with colors that indirectly help in the rehabilitation process of juvenile delinquents in Malaysia.